Editor's choice: risk of stroke before revascularisation in patients with symptomatic carotid stenosis$da pooled analysis of randomised controlled trials - Fisch, Urs; von Felten, Stefanie; Wiencierz, Andrea; Jansen, Olav; Howard, George; Hendrikse, Jeroen; Halliday, Alison; Fraedrich, Gustav; Eckstein, Hans-Henning; Calvet, David; Bulbulia, Richard; Becquemin, Jean-Pierre; et al. (European journal of vascular and endovascular surgery, 2021)
Objective - Current guidelines recommending rapid revascularisation of symptomatic carotid stenosis are largely based on data from clinical trials performed at a time when best medical therapy was potentially less effective than today. The risk of stroke and its predictors among patients with symptomatic carotid stenosis awaiting revascularisation in recent randomised controlled trials (RCTs) and in medical arms of earlier RCTs was assessed. - Methods - The pooled data of individual patients with symptomatic carotid stenosis randomised to stenting (CAS) or endarterectomy (CEA) in four recent RCTs, and of patients randomised to medical therapy in three earlier RCTs comparing CEA vs. medical therapy, were compared. The primary outcome event was any stroke occurring between randomisation and treatment by CAS or CEA, or within 120 days after randomisation. - Results - A total of 4 754 patients from recent trials and 1 227 from earlier trials were included. In recent trials, patients were randomised a median of 18 (IQR 7, 50) days after the qualifying event (QE). Twenty-three suffered a stroke while waiting for revascularisation (cumulative 120 day risk 1.97%, 95% confidence interval [CI] 0.75 - 3.17). Shorter time from QE until randomisation increased stroke risk after randomisation (χ2 = 6.58, p = .011). Sixty-one patients had a stroke within 120 days of randomisation in the medical arms of earlier trials (cumulative risk 5%, 95% CI 3.8 - 6.2). Stroke risk was lower in recent than earlier trials when adjusted for time between QE and randomisation, age, severity of QE, and degree of carotid stenosis (HR 0.47, 95% CI 0.25 - 0.88, p = .019). - Conclusion - Patients with symptomatic carotid stenosis enrolled in recent large RCTs had a lower risk of stroke after randomisation than historical controls. The added benefit of carotid revascularisation to modern medical care needs to be revisited in future studies. Until then, adhering to current recommendations for early revascularisation of patients with symptomatic carotid stenosis considered to require invasive treatment is advisable.
Available online 5 April 2021
Gesehen am 03.08.2021